Conversion in the Building of Substantives of the Old Byelorussian Language - Закарьян, М. (Kalbotyra, 1980)
The object of the article is the building of substantives by means of external (between the parts of speech) and internal (inside one part of speech) conversion in the Old Byelorussian language of the end of the 16th-the beginning of the 17th century.It is concluded that the change of the system of flexions is also characteristic of the affixal word-building, but it is an accompanying phenomenon. and in default of affixes this change of the paradigm becomes the main means of word-building.